Simple and clean determination of tetracyclines by flow injection analysis - Rodríguez, Michael Pérez [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B. V., 2015)
An environmentally reliable analytical methodology was developed for direct quantification of tetracycline (TC) and oxytetracycline (OTC) using continuous flow injection analysis with spectrophotometric detection. The method is based on the diazo coupling reaction between the tetracyclines and diazotized sulfanilic acid in a basic medium, resulting in the formation of an intense orange azo compound that presents maximum absorption at 434nm. Experimental design was used to optimize the analytical conditions. The proposed technique was validated over the concentration range of 1 to 40μgmL(-1), and was successfully applied to samples of commercial veterinary pharmaceuticals. The detection (LOD) and quantification (LOQ) limits were 0.40 and 1.35μgmL(-1), respectively. The samples were also analyzed by an HPLC method, and the results showed agreement with the proposed technique. The new flow injection method can be immediately used for quality control purposes in the pharmaceutical industry, facilitating monitoring in real time during the production processes of tetracycline formulations for veterinary use.
Keywords: Flow injection analysis (fia); Green chemistry; Quantification; Spectrophotometry; Tetracyclines; Veterinary pharmaceuticals